The Methodological Quality of Studies Investigating the Acute Effects of Exercise During Hypoxia Over the Past 40 years: A Systematic Review - Hohenauer, Erich; Freitag, Livia; Herten, Miriam; Siallagan, Julia; Pollock, Elke; Taube, Wolfgang; Clijsen, Ron (Frontiers in Physiology, 2022)
Exercise under hypoxia and the physiological impact compared to normoxia or hypoxia has gained attention in the last decades. However, methodological quality assessment of articles in this area is lacking in the literature. Therefore, this article aimed to evaluate the methodologic quality of trials studying exercise under hypoxia. An electronic search was conducted until December 2021. The search was conducted in PubMed, CENTRAL, and PEDro using the PICO model. (P) Participants had to be healthy, (I) exercise under normobaric or hypobaric hypoxia had to be (C) compared to exercise in normoxia or hypoxia on (O) any physiological outcome. The 11-item PEDro scale was used to assess the methodological quality (internal validity) of the studies. A linear regression model was used to evaluate the evolution of trials in this area, using the total PEDro score of the rated trials. A total of n=81 studies met the inclusion criteria and were processed in this study. With a mean score of 5.1±0.9 between the years 1982 and 2021, the mean methodological quality can be described as “fair”. Only one study reached the highest score of 8/10 and n=2 studies reached the lowest observed value of 3/10. The linear regression showed an increase of the PEDro score of 0.1 points per decade. A positive and small tendency towards increased methodologic quality was observed. The current results demonstrate that a positive and small tendency can be seen for the increase in the methodological quality in the field of exercise science under hypoxia. A “good” methodological quality, reaching a PEDro score of 6 points can be expected in the year 2063, using a linear regression model analysis. To accelerate this process, future research should ensure that methodological quality criteria are already included during the planning phase of a study.